20% External Quantum Efficiency in Solution‐Processed Blue Thermally Activated Delayed Fluorescent Devices. (15th October 2015) - Cho, Yong Joo; Chin, Byung Doo; Jeon, Sang Kyu; Lee, Jun Yeob
Abstract : Highly efficient solution‐processed blue thermally activated delayed fluorescent (TADF) devices are developed by designing soluble blue TADF emitters. The solubility and emission color could be managed by introducing F as an electron withdrawing unit instead of CN. Two soluble blue TADF emitters are synthesized and show a high external quantum efficiency of 20.0% with a color coordinate of (0.16, 0.26), and it is the best quantum efficiency reported in solution‐processed TADF devices. The device performances of the solution‐processed blue TADF devices are comparable to those of vacuum‐processed blue TADF devices. Abstract : A high quantum efficiency of 20% in blue, solution‐processed, thermally activated delayed fluorescent devices is achieved by developing blue emitters with an F functional unit instead of CN functional unit.